1999
DOI: 10.1144/0050501
|View full text |Cite
|
Sign up to set email alerts
|

Sedimentary basins and petroleum systems offshore Newfoundland and Labrador

Abstract: The sedimentary basins offshore Newfoundland and Labrador include those related to the opening and closing of the Palaeo-Atlantic (Iapetus) Ocean and those formed during the opening of the present Atlantic Ocean.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 16 publications
(11 reference statements)
0
7
0
Order By: Relevance
“…The ridges are considered to be extrusive volcanic edifices which were subsequently draped with sedimentary rocks until finally being overstepped by sediment in Eocene time (Scrutton and Bentley, 1988). The stratigraphic control does not allow them to be dated accurately but they may be of Early Cretaceous age, when there was also significant igneous activity in the Porcupine Basin and on the Labrador Margin (Scrutton and Bentley, 1988;Tate and Dobson, 1988;Balkwill, 1987;DeSilva, 1999). Although the seismically-imaged ridges appear extrusive, modelling by Scrutton and Bentley (1988) indicated that the magnetic anomalies are best explained by a combination of the extrusive units and underlying intrusions, presumably lying along the fissures through which the igneous rocks were emplaced.…”
Section: Rockall Basinmentioning
confidence: 99%
“…The ridges are considered to be extrusive volcanic edifices which were subsequently draped with sedimentary rocks until finally being overstepped by sediment in Eocene time (Scrutton and Bentley, 1988). The stratigraphic control does not allow them to be dated accurately but they may be of Early Cretaceous age, when there was also significant igneous activity in the Porcupine Basin and on the Labrador Margin (Scrutton and Bentley, 1988;Tate and Dobson, 1988;Balkwill, 1987;DeSilva, 1999). Although the seismically-imaged ridges appear extrusive, modelling by Scrutton and Bentley (1988) indicated that the magnetic anomalies are best explained by a combination of the extrusive units and underlying intrusions, presumably lying along the fissures through which the igneous rocks were emplaced.…”
Section: Rockall Basinmentioning
confidence: 99%
“…Most of the sedimentary basins underlying the margins of the North Atlantic contain discovered or producing oil and gas fields or contain potential hydrocarbon source rocks (Butterworth, Holba, Hertig, Hughes, & Atkinson, 1999;DeSilva, 1999;Roberts et al, 1999;Spencer, Birkeland, Knag, & Fredsted, 1999;Williams et al, 1999). A pre-rift continental refit of the circum North Atlantic region for the Mesozoic, before the opening of the North Atlantic Ocean (e.g.…”
Section: Mesozoicmentioning
confidence: 99%
“…The Cartwright Formation is a lateral equivalent to the Gudrid Member and is interpreted to comprise submarine sandstones. The Gudrid Sandstone is interpreted to represent redeposited eroded material from the Markland Delta (DeSilva, 1999).…”
Section: O F F S H O R E / O T Cmentioning
confidence: 99%
“…The top of the Kenamu Formation is characterized by fine-grained sandstones of the Lief Member. The Leif Member is interpreted as a shallow-marine sandstone deposited toward the latter stages of seafloor spreading (DeSilva, 1999;Chalmers and Pulvertaft, 2001).…”
Section: O F F S H O R E / O T Cmentioning
confidence: 99%